2018
DOI: 10.1016/j.jtcme.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of salep against isoniazid liver toxicity in wistar rats

Abstract: IntroductionIsoniazid is a drug for treatment of tuberculosis. One of the main side effects of this drug is hepatotoxicity, which is a major cause of treatment interruption in tuberculosis. This study is about the preventive effect of Salep on this side effect of isoniazid.Materials and methodsThis study is an experimental study in which the preventive effect of salep on isoniazid hepatotoxicity is evaluated. In this study 56 rats were randomly placed in 7 eight members groups including: control group, sham, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Histological examination of liver sections in high methionine rats showed marked alterations in the liver tissue, as inflammatory cells infiltration, ballooned hepathocytes, necrosis and sinusoid hemorrhage. These observations are similar to others 27 , 28 . Furthermore, altered liver structure confirmed the release of hepatic proteins in plasma as outlined above.…”
Section: Discussionsupporting
confidence: 93%
“…Histological examination of liver sections in high methionine rats showed marked alterations in the liver tissue, as inflammatory cells infiltration, ballooned hepathocytes, necrosis and sinusoid hemorrhage. These observations are similar to others 27 , 28 . Furthermore, altered liver structure confirmed the release of hepatic proteins in plasma as outlined above.…”
Section: Discussionsupporting
confidence: 93%
“…Antioxidant and anti-inflammatory impacts of BSE have been reported in several studies (18,19). Kushwah et al (20) have reported decreased serum liver-specific enzymes and malondialdehyde and increased antioxidant enzymes in the liver following BSE treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The environment dark and light cycle and the humidity were at standard rate, 12/12 hr and 50-55%, respectively. According to previous articles, the prescribed concentration was 40, 80, 160, and 320 mg/kg of body weight (19,20). Therefore, the control and experimental groups in this study include healthy control groups 1 and 2: without receiving any substance and under normal conditions for 60 and 89 days, respectively.…”
Section: Test Designmentioning
confidence: 99%